English Proficiency And Computer Literacy Of Malaysian Polytechnic Civil Engineering Students - Yasin, Ahmad Yasruddin Md (2007)
The purpose of this study was to investigate the English proficiency and computer literacy of Malaysian polytechnic civil engineering students. A questionnaire, modeled after the Programme for International Student Assessment (PISA) approach was developed and administered to 480 civil engineering students from six polytechnics. These students had completed a mandatory one-semester industrial training programme with various organizations. This post industrial training survey, through the use of a self-report questionnaire called the Malaysian Polytechnic Employability Skills Questionnaire (MPESQ) provided an important opportunity to capture crucial data from students such as their acquired (actual) and required skills in both the English language and computer-related subjects.